Instalações Militares de Energia Zero: avaliação técnica para quartéis do Exército Brasileiro com sistemas fotovoltaicos e sistemas de armazenamento de energia - Silva Neto, Luiz Pereira da (2021)
One of the ways to assure the energy supply in military installations is applying the zero-energy concept in bases with photovoltaic plus storage systems. Taking advantage of the growth of distributed generation in Brazil, especially with photovoltaic generation, and with the forecast of an increase in the use of storage systems by prosumers, this work technically analyzed the performance of photovoltaic systems integrated in roofs of Brazilian Army military buildings coupled to electrical energy storage systems. The simulations were conducted using System Advisor Model (SAM) and the three on-grid clusters considered as case studies are placed in Manaus, AM, Campo Grande, MS and Ponta Grossa, PR. The performances of two photovoltaic cell technologies were analyzed (mc-Si and CdTe) and the coupling of PV to storage systems were made in two ways (DC- or AC-coupling). Systems with CdTe resulted in higher yields and PR in all locations, being the most recommended technology for integration in the three clusters. The performance differences were more accentuated in the warmer climate and smaller in the milder climate. The difference between cell operating temperatures and ambient temperature was identified as a factor that reduces performance. Photovoltaic systems generated an amount of energy greater than consumption ranging from 8% to 25%. Four scenarios were considered, varying the capacity and dispatch of the storage systems: Baseline, Peak, Night, and Day, which were evaluated according to the Self-Consumption Rate and the Self-Sufficiency Rate. Without storage systems, both indicators were approximately 40% in most cases. These indicators increased as storage systems with high capacities and large energy dispatch time were coupled (approximately 50% in the Peak Scenario, 80% in the Night Scenario, and over 90% in the Day Scenario). The energy balance calculated for the purpose of zero energy classification considered the interactions with the grid and, therefore, accounted for the compensation of imported energy with different Credit Compensation Factors. In scenarios with losses in the compensable portion of exported energy, only storage systems with high storage capacities and a wide dispatch period configuration were able to make the energy balances positive, enabling the classification of the three clusters as Energy Positive Military Installations. Key-words: hybrid systems; AC coupling; DC coupling; defense; energy compensation; Lithium ions batteries; self-sufficiency; self-consumption; dirt losses